From Novice to Native-Like: How Diphthongs Are Pronounced? Dari Pemula menuju Kemahiran Seperti Penutur Asli: Bagaimana Diftong Diartikulasikan oleh Penutur? - Nike Angraini (DARMADIKSANI, 2026)
English pronunciation is seen to be one of the most crucial aspects in the English language setting because proper and correct pronunciation creates effective and efficient means of communication. This community empowerment was implemented to investigate the effect of English phonetics transcription instruction, particularly on diphthongs, to boost EFL learners’ English pronunciation. Thirteen participants, of which teemed by female, were taken in such a convenient way. One of orphanages in South Sumatera, Palembang was chosen to be empowered in this activity. To check EFL learners’ English pronunciation achievement, an English pronunciation test was provided as a pre-test and a post-test. The results revealed that English phonetics transcription instruction impacted EFL learners’ English pronunciation attainment, particularly diphthongs. This could be viewed from t obtained value which was much higher than the t table (2.497 > 2.179) and the p value gained was much lower than .05 (.02 < .05). In addition, other instructors, agents of change, future facilitators, and participants were imparted with fruitful implications due to the implementation of English pronunciation instruction to have a native-like communication to some extent.